Role of MicroRNA in the Diagnosis and Therapy of Hepatocellular Carcinoma: A New Frontier - Tsoulfas, Georgios (MicroRNA, 2014)
The incidence of hepatocellular carcinoma continues to increase worldwide, representing one of the premier causes of cancer-related deaths. It is closely related to liver fibrosis and cirrhosis (and their underlying etiologies), thus making its treatment a challenge, as one has to simultaneously manage both the liver disease, as well as the malignancy. Although there are a variety of different therapies proposed, the two main ones that can actually lead to a therapeutic result, are surgical resection and orthotopic liver transplantation. However, the challenge remains in terms of early diagnosis of the disease, identifying the steps that lead to its progression and choosing the best treatment for each patient. Regarding this latter comment, it has been determined that not all cancers are the same, in the sense that their molecular make-up and alterations are what dictate their specific behavior and aggressiveness; which would be helpful to know if the goal is to choose a patient- and tumor-oriented individualized approach, that will yield better results. Critical in this effort has been and continues to be the role of microRNA, which appears to play a central role in the progression, diagnosis and management of hepatocellular carcinoma. This paper will attempt to clarify the role of microRNA in these areas and provide a window to the future.
Keywords: surgical resection